BAHASA, IDENTITAS, DAN KITAB SUCI: TERJEMAHAN AL-QUR’AN DALAM BAHASA PALEMBANG DAN MANDAR SOSIOLINGUISTIK BENCHMARKING - Darsita Suparno; Siti Amsariah; Fajriaty Jamiyl; Akbar Amanah Illahi Chairul
The translation of the Qur’an into local languages plays a strategic role in strengthening local linguistic identities in Indonesia and facilitating access to the holy text’s comprehension amidst the dominance of the national and global languages. However, studies on the translation of the Qur’an in the contexts of Palembang and Mandar in South Sulawesi remain limited, particularly concerning the dynamics of language identity, language attitudes, and the preservation of local languages. This study aims to examine the challenges and strategies in translating the Qur’an into Indonesian, Palembang, and Mandar, using a sociolinguistic approach to explore how these translations reflect the construction of linguistic identity among native speakers of these local languages. This study employs a qualitative method with a document analysis approach focusing on the official Qur’an translation texts published by the Ministry of Religious Affairs, along with critical discourse analysis to identify translation strategies and ideological representations within the texts. The findings indicate that the translation of the Qur’an into local languages not only faces sociolinguistic, and theological challenges but also serves as a site for constructing linguistic identity that strengthens ethnolinguistic solidarity. The translation strategies employed, including cultural adaptation and communicative approaches, effectively enhance local communities’ comprehension of the holy text while simultaneously fostering a sense of belonging to their local languages. This study highlights the importance of language policies that support the sustainable translation of sacred texts into local languages as a means of preserving linguistic diversity and reinforcing cultural identity within the context of globalization.